Relevance Of Covid-19 Media Message Protocols Among Rural Dwellers in South, West, Nigeria - Okioya, Solomon Ojo; Tejumaiye , Adepoju Joseph; Ogundeji, Kayode Benjamin (Corpus Intellectual, 2025)
The aim of this study was to examine COVID-19 media message protocols among rural dwellers in South West Nigeria. It ascertained the influence of the media messages on the people of South West, Nigeria after the pandemic in 2020 and also accessed the types of media messages the rural dwellers are exposed to for the government protocols. The study was anchored on three theories: diffusion innovation theory, development media theory and modernization theory. The study adopted the mix methods approach by using survey design with in-depth interviews to administer questionnaire to respondents which cut across three Senatorial Districts of Ondo, Osun and Ekiti states. These include Elegbeka from Ondo North, Jegele from Ondo Central and Aiyede for Ondo South, Akoda from Osun West, Obaloja from Osun Central and Ipole from Osun East, Ugbo- Aro from Ekiti South, Orin from Ekiti North and Ogotun from Ekiti Central Senatorial Districts. Out of a total population of 13,344600, a sample size of 900 questionnaires was administered to the respondents out of which 722 were returned and used for data analysis. The finding shows that the respondents were aware ofCOVID-19 and believed it was a real pandemic. This showed that government and health authorities were successful in creating awareness on the disease even in hard-to-reach areas like the rural areas. Results also revealed that radio was the most accessible medium useful in disseminating health information to rural areas. Another finding revealed that most rural dwellers accepted media message on COVID-19 but had little attitude towards adopting the media messages protocols on COVID-19. The study concluded that Nigerians are highly desirous of information pertaining to the novel COVID-19 virus messages on treatment protocols and home remedies for prevention/treatment of the pandemic should be disseminated through relevant media. It was also concluded that media messages and health information are essential tools to fight against pandemic among the rural dwellers and the government need to give more attention to the health situation of rural areas. It therefore recommended among others that the culture of the various rural communities should be considered before arriving on which protocols to be introduced to the rural dwellers and that with the easing of the pandemic, people are now living a care free life, ignoring CO VID-119 protocols in spite of the worries about the second wave of the disease, the enforcement team should be constituted not only at the urban centers but also in every rural area of the country.